GAS TURBINE UNITE INLET AIR COOLING BY USING AN EXCESSIVE REFRIGERATION CAPACITY OF ABSORPTION-EJECTOR CHILLER IN BOOSTER AIR COOLER - Андрій Миколайович Радченко; Сергій Анатолійович Кантор; Богдан Сергійович Портной; Юрій Георгійович Щербак (Авіаційно-космічна техніка та технологія, 2018)
The processes of gas turbine unit two-stage intake air cooling by absorption lithium-bromide chiller as a high temperature cooling stage to the temperature of about 15 °C and by refrigerant ejector chiller as a low temperature cooling stage to the temperature of about 10 °C through utilizing the turbine exhaust gas waste heat for hour-by-hour changing ambient air temperatures and changeable heat loads on the air coolers as consequence during 10 days of July 2017 (10–12.07.2017) for climatic conditions of the south of Ukraine are analyzed. The computer programs of the firms-producers of heat exchangers were used for gas turbine unit inlet air cooling processes simulation. It is shown that at decreased heat loads on the air coolers an excessive refrigeration capacity of combined absorption-ejector chiller exceeding current heat loads is generated which can be used for covering increased heat loads on the air coolers and to reduce the refrigeration capacity of the absorption-ejector chiller. To solve this task the refrigeration capacity required for gas turbine unit inlet air cooling is compared with an excessive refrigeration capacity of the absorption-ejector chiller exceeding current heat loads summarized during 10 days. The system of gas turbine unit inlet air cooling with a booster stage of precooling air and a base two-stage cooling air to the temperature of about 10 °C by absorption-ejector chiller has been proposed. An excessive refrigeration capacity of the absorption-ejector chiller generated during decreased heat loads on the gas turbine unit inlet air coolers that is collected in the thermal accumulator is used for gas turbine unit inlet air precooling in a booster stage of air coolers during increased heat loads on the air coolers. The results of gas turbine unit inlet air cooling processes simulation proved the reduction of refrigeration capacity of the absorption-ejector chiller by about 50 % due to the use of a booster stage for precooling air at the expanse of an excessive absorption-ejector chiller refrigeration capacity served in the thermal accumulator. The conclusion has been made about the efficient use of a booster stage of gas turbine unit inlet air cooler for precooling air by using an excessive refrigeration potential of absorption-ejector chiller saved in the thermal accumulator